Anaerobic digestion of biowaste under extreme ammonia concentration: Identification of key microbial phylotypes. (May 2016) - Poirier, Simon; Desmond-Le Quéméner, Elie; Madigou, Céline; Bouchez, Théodore; Chapleur, Olivier
Graphical abstract: Highlights: Microbial community shifts were investigated from 0.0 up to 50.0 g/L of TAN. Ultimate CH4 yield was not impaired by TAN up to 25.0 g/L. Methanosarcina populations were present up to 25.0 g/L of TAN. Treponema relative abundance increased with TAN concentration up to 10.0 g/L. Abundant Caldicoprobacter populations detected from 5.0 up to 25.0 g/L of TAN. Abstract: Ammonia inhibition represents a major operational issue for anaerobic digestion (AD). In order to get more insights into AD microbiota resistance, anaerobic batch reactors performances were investigated under a wide range of Total Ammonia Nitrogen (TAN) concentrations up to 50.0 g/L at 35 °C. The half maximal inhibitory concentration (IC50 ) value was determined to be 19.0 g/L. Microbial community dynamics revealed that above a TAN concentration of 10.0 g/L, remarkable modifications within archaeal and bacterial communities occurred. 16S rRNA gene sequencing analysis showed a gradual methanogenic shift between two OTUs from genus Methanosarcina when TAN concentration increased up to 25.0 g/L. Proportion of potential syntrophic microorganisms such as Methanoculleus and Treponema progressively raised with increasing TAN up to 10.0 and 25.0 g/L respectively, while Syntrophomonas and Ruminococcus groups declined. In 25.0 g/L assays, Caldicoprobacter were dominant. This study highlights the emergence of AD key phylotypes at extreme ammonia concentrations.